Ekranisasi Pada Novel ke dalam Film the Great Gatsby Karya F Sott Fitzgerald - Lenggo Geni (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Literature is born from the human desire to express their existence, which is closely related to the relationship between individuals and with the reality of life. A literary work contains specific intentions and purposes set by the author. Therefore, all aspects of a literary work originate from the author, who plays a crucial role in generating creative ideas that are expressed through their writings.In line with technological advancements, literature has also undergone transformation. One of the indicators of this progress is the emergence of intersemiotic transfer or adaptation, namely the process of changing the medium through which a literary work is presented, such as from text to audiovisual or film. In this context, the researcher examines the adaptation process from novel to film as the object of study.The object of this research is the novel The Great Gatsby by F. Scott Fitzgerald, which was later adapted into a film by director Baz Luhrmann, released in 2013 under the same title. The novel portrays the life of the American upper class during the 1920s, an era often referred to as the Roaring Twenties.This study uses a descriptive qualitative method. Qualitative research aims to describe and analyze social phenomena and activities found in the research object. The data were collected through reading, observing, and note-taking techniques, involving both the novel and the film script. In total, the researcher collected 12 data points from the analysis of the novel and its film adaptation.